OPTIMASI STRUKTUR UNTUK MENDAPATKAN FREKUENSI ALAMI YANG TERPISAHKAN SECARA OPTIMAL - Soemantri B, Satryo; Suweca, I Wayan; Sujatmika, Endra (Mesin, 1998)
In obtaining the dynamic response of a dynamic system, its uncouple modal equation of movement simplifies the usage of superposition modal method. This paper proposes a strategy to obtain the uncouple modal equation based an hypotheses of Basile : âAlthough the presence of modal-damping-couple, the modal equations of movement are dynamically uncoupled for a structure having small damping coefficient if its natural frequencies are well-separated